Dystopian Literature as a Tribune for Social Therapy: Ray Bradbury’s Fahrenheit 451(1953) - Labgaa ,Nadjoua; Selt ,Djihad Afafa (Faculty of Letters and Foreign Languages Department of English, 2018)
This project represents a closer examination on the relationship between literature and society. It investigates the role of literature in society. The purpose of this study is to examine the effects of literature, particularly dystopian literature, on society’s development. Furthermore, this study, which adopts an analytical approach, sheds light on the importance of books and literature in individual’s life in particular, and in society in general. Ray Bradbury’s Fahrenheit 451 (1953) portrays the suffering of characters because of the lack of books. Characters, as the protagonist, seek the real happiness, freedom, and peace. The struggle of these characters lies in the fact of finding answers to their doubts under a totalitarian authority. By the end, literature seems to be the only solution for Montag, the protagonist, to get rid of such authoritative regime. Hence, literature, dystopian genre, as a social therapy is been proved by Bradbury’s novel. Correspondingly, with literature, society will be remediated.